Denmark : Selected Background Issues. (IMF Staff Country Reports; Country Report, 1995)
This Selected Background Issues paper analyzes the transformation of Denmark's current account during 1960-94. The paper highlights that in 1990, Denmark recorded its first current account surplus in almost thirty years. This ended three decades where the Danish economy was seemingly able to ignore the implications of intertemporal budget constraints by borrowing continually to finance successive current account deficits. This paper attempts to address some questions in explaining how this transformation of the external position was achieved.